The Mediating Role of Technological Support in Enhancing Employee Productivity and Job Satisfaction through Remote Work Policies in Indonesia - Alam, Andi Aminullah; Dewi, Erni Ratna (Universitas Muhammadiyah Yogyakarta, 2024)
Research aims: The COVID-19 pandemic has accelerated the adoption of remote work globally, including in Indonesia. This study investigates the impact of remote work policies on employee productivity and job satisfaction in Indonesia, with an emphasis on the mediating role of technological support.Design/Methodology/Approach: Using a sample of 300 respondents from various industries, we employed Structural Equation Modeling (SEM) to analyze the data.Research findings: The results indicate that remote work positively influences both employee productivity and job satisfaction. Furthermore, technological support significantly enhances these effects, underscoring its critical role in successful remote work implementation.Theoretical Contribution/Originality: The findings extend the Job Demands-Resources (JD-R) model by highlighting the critical mediating role of technological support in enhancing the positive impacts of remote work policies on employee productivity and job satisfaction.Practitioners/Policy Implications: These findings provide valuable insights for policymakers and business leaders aiming to optimize remote work strategies through effective technological investments.Research Limitations/Implications: This study's primary limitation is the reliance on self-reported data from a specific geographic region, which may not fully capture the diverse experiences and technological infrastructures present in other parts of Indonesia.